Role of drug eluting stents in diabetic patients. Issue 5 (31st January 2006) - Boccara, F; Teiger, E; Cohen, A
Abstract : There is a clear need for a large multicentre trial comparing the efficacy of the two available drug eluting stents, sirolimus and paclitaxel, in diabetic patients with multivessel disease